Diagnosis dan Tatalaksana Paroxysmal Nocturnal Hemoglobinuria - -, Cecile (Cermin Dunia Kedokteran, 2021)
Paroxysmal nocturnal hemoglobinuria (PNH) merupakan kelainan sel hematopoesis didapat yang menyebabkan hemolisis intravaskular dan berisiko tinggi trombosis. PNH terdiri dari PNH klasik, PNH terkait kegagalan sumsum tulang dan PNH subklinis. Diagnosis PNH dengan flow cytometry (FCM). Terapi PNH saat ini menggunakan eculizumab, ravulizumab dan transplantasi sel punca alogenik.Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired disorder of hematopoietic stem cell causing intravascular hemolysis and high risk of thrombosis. It can be differentiated into: classical PNH, PNH associated with bone marrow failure and subclinical PNH. Diagnosis is made by flow cytometry. PNH is treated with eculizumab, ravulizumab and allogenic stem cell transplantation.